TRADISI RASULAN DI KP. BOJONG DESA KEMUNING KECAMATAN TUNJUNG TEJA SERANG-BANTEN (LIVING HADIS) - Anggi Anggi; Muhammad Alif (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
Rasulan is a tradition in Bojong Village, which is one of the areas in Serang Regency, Banten Province. This tradition is called the Apostle because it is often carried out on Islamic holidays, especially in the month of the Prophet’s birthday. This Apostle did it as an expression of gratitude to Allah SWT for the abundance of rice harvest and also a form of almsgiving. In Bojong Village, this apostolic tradition has a meaning that is passed down from generation to generation, namely as a form of gratitude to Allah SWT. in addition, the local community views this issue as a sacred moment that unites religious values, customs, and togetherness. Which contains various Kinds such as joint Prayer, Selametan, an Eating Together. This reaserch uses a qualitative approach with a descriptive-interpretive type of reaserch and is based on social action theory. The qualitative approach was chosen because this study aims to deeply understand the meaning, Values, and social actions of the community in the apostolic tradition as a living religious practice (living hadith) in Bojong Village, Kemuning Village, Tunjung Teja District, Serang-Banten Regency. Social action theory is used to analyze how community actions in the Apostolic traditon are underpinned by subjective meanings related to religious values, customs, and social relations. The tradition of the Apostles in Bojong Village forms a social system that regulates the pattern of relationships and interactions between residents.